EVOLUTION OF LIPOSOMAL CARRIERS INTENDED TO ANTICANCER DRUG DELIVERY: AN OVERVIEW - ESTANQUEIRO, MARILENE; AMARAL, MARIA HELENA; CONCEICAO, JAIME; LOBO, JOSE MANUEL SOUSA (International Journal of Current Pharmaceutical Research, 2015)
Most current anticancer agents are present lack of specificity, leading to systemic toxicity and adverse effects, and limiting the maximum dose of drug. Liposomes quickly passed from a simple scientific curiosity to magic bulletsâ€ for the delivery of drugs. Liposomal formulations of anticancer drugs have been extensively evaluated, with notorious advances and the market introduction of some of them. In the last years, the research under liposomes has been carried out to increase the circulation time and the specificity to cancer cells. The aim of this work was to make a review about the research carried out about the application of liposomes as carriers for anticancer drugs. Liposomal formulations of anticancer drugs have been extensively evaluated. However, many other liposome based carriers were studied, like immuno liposomes, thermossensitive liposomes, dual functional liposomes and cross linked multifunctional liposomes, intended to increase drug specificity. Additionally, some special types of liposomes, like niosomes, transfersomes and ethosomes were also investigated as cytotoxic drug carriers.